A survey on software test automation return on investment, in organizations predominantly from Bengaluru, India. (16th December 2021) - Reine De Reanzi, S.; Ranjit Jeba Thangaiah, P.
Software industry has adopted automated testing widely. The most common method adopted is graphical user interface test automation for the functional scenarios to reduce manual testing and increase the repeatability. Reducing execution time and redundancy to achieve quality "go/no go decisions" provides rational for the executive management to allocate funds to adopt automation and invest in the setup including people, process, and tools to achieve faster time to market. There are a variety of practices engaged by testers, like frameworks, tools, methods, procedures, models, and technologies to achieve automation. Nonetheless, the actual effectiveness in terms of return on investment (ROI) is not known, though there are various formulas to calculate ROI of test automation. The factors that determine the ROI are maturity of test automation, purpose, or intent, picking right tests for automation, knowledge of the tester to derive test coverage, domain expertise, defining right metrics like defects found by automation runs, cost versus reduction of time, labor versus quality of scripts, repeatability, and results. These factors form the base of the questions designed for the survey. The paper presents a survey and analysis to understand the ROI of test automation from industry test professionals from both product and services organizations.